OPTIMIZATION OF TREATMENT OF ISOLATED BURNS OF THE HAND AND FOOT - Avazov A. A.; Shakirov B. M.; Karabaev J. Sh. (Web of Journals Publishing, 2024)
The study was conducted on data from the examination and treatment of 81 victims with deep burns of the hands and feet. Silver-containing preparations were applied to the wound surfaces, after which the limbs were placed in plastic bags (group I, n=46). In some patients (group II, n=35), wounds were treated using the traditional method with various ointments and solutions. Every day, accumulated liquid was removed from the bags, its volume was measured and subjected to biochemical analysis. Silver cream-containing preparations were replaced with a new one. After stopping the flow of plasma through the wound surfaces and cleaning the wounds from fibrin deposits, treatment was carried out using ointment dressings.
Keywords: Silver-containing preparations, cysts and foot, moist environment.